Facilitators of the transition process for the self-care of the person with stoma: subsidies for Nursing - Marina Soares Mota; Giovana Calcagno Gomes; Vilma Madalosso Petuco; Rita Maria Heck; Edaiane Joana Lima Barros; Vera Lúcia de Oliveira Gomes (SciELO, 2015)
OBJECTIVE To know the facilitating factors of the transition process from dependency to the self-care of people with a stoma. METHOD This is a descriptive study of qualitative approach, including 27 people with permanent stomas due to cancer. The data were collected through semi-structured interviews and submitted to content analysis based on the Transition Theory as theoretical reference. RESULTS The self-care facilitators related to the person were the positive significance of ostomy; the preparation for this experience already in the preoperative period; emotional stability; faith; religiousness; and a sense of normalcy acquired from a next image similar to the previous one. The facilitators related to the community were the following: receiving equipment for free from the government; support from family and the multidisciplinary team, especially the nurses; and having contact with other people with stomata. CONCLUSION The results allow that nurses develop strategies to help people with stomata to resume their self-care.